1996
DOI: 10.1111/j.1476-5381.1996.tb15999.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of angiotensin II type 1 receptor blockade and angiotensin‐converting enzyme inhibition in pregnant sheep during late gestation

Abstract: 1 The effects of antagonism of the maternal renin-angiotensin system (RAS) with either an angiotensin II type 1-(ATI) specific receptor blocker (GR138950) or an angiotensin-converting enzyme (ACE) inhibitor (captopril) 9 The present study demonstrated that administration of either GR138950 or captopril to pregnant ewes effectively blocked the maternal RAS, and caused hypotension and a decrease in uterine blood flow. However, only captopril appeared to cross the placenta to influence directly the RAS of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…Recent work has demonstrated that administration of GR 1 38950 to pregnant ewes during late gestation causes maternal hypotension and abolishes the maternal pressor response to exogenous All (Forhead et al 1996). These effects occur without influencing basal blood pressure, or the pressor response to All, in the sheep fetus (Forhead et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work has demonstrated that administration of GR 1 38950 to pregnant ewes during late gestation causes maternal hypotension and abolishes the maternal pressor response to exogenous All (Forhead et al 1996). These effects occur without influencing basal blood pressure, or the pressor response to All, in the sheep fetus (Forhead et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These effects occur without influencing basal blood pressure, or the pressor response to All, in the sheep fetus (Forhead et al 1996). GR138950, however, has been detected in the fetal circulation, albeit at low concentrations, within 2 h of maternal administration and is associated with a decrease in fetal oxygenation (Forhead et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations